Preclinical study to improve microbubble-mediated drug delivery in cancer using an ultrasonic probe with an interchangeable acoustic lens - Lee, Seunghyun; Jeon, Hoyoon; Shim, Shinyong; Im, Maesoon; Kim, Jinsik; Kim, Jung Hoon; Lee, Byung Chul (Nature Publishing Group, 2021)
Focused ultrasound with microbubbles (FUS-MBs) has shown that it can lead to an efficient drug delivery system (DDS) involving the oscillation and destruction of the MB but is limited in drug delivery due to its narrow pressure field. However, unfocused ultrasound with MBs (UUS-MBs) and an interchangeable acoustic lens can tune and enhance the pressure field for MB destruction to overcome the disadvantages of FUS-MB DDSs. We designed a lens suitable for an ultrasound-phased array probe and studied the optimal treatment conditions for MB destruction in vitro through an optical imaging setup. The DDS effects were evaluated in a rat hepatoma model using doxorubicin (DOX) treatment. A concave lens with a radius of curvature of 2.6 mm and a thickness of 4 mm was selected and fabricated. UUS-MBs with the acoustic lens at 60 V-pp for 32 cycles and a PRF of 1 kHz could induce MB destruction, promoting the DDS even under fluidic conditions. In the animal experiment, the UUS-MBs in the acoustic lens treatment group had a higher concentration of DOX in the tumor than the control group. Our system suggests uses an acoustic lens to increase DDS effectiveness by providing sufficient ultrasound irradiation to the MBs.